An examination of Alfred North Whitehead’s “Philosophy of Organism” to determine compatibility with contemporary arguments for the primacy of process in science of biology : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Philosophy at Massey University, Distance, New Zealand - Wilson, Michael Paul (Massey University, 2024)
Alfred North Whitehead’s ‘Philosophy of Organism’ is a philosophy that does not deny the existence of things in the world such as tables and chairs, but asserts that everything is ultimately made of processes. The purpose of this thesis is to understand better whether Whitehead’s philosophy is relevant to contemporary process philosophers of biology. John Dupré and Daniel Nicholson are examples of contemporary philosophers of biology who claim that living beings should be viewed as ‘processes’, as Whitehead envisaged, and not as “things” or “substances”. Specifically, we are interested in those topics associated with process ontology and epistemology in the context of the science of biology. The thesis is composed of four parts. The first chapter provides an overview of the historical background of process philosophy and the issues that arose in its development. The second chapter examines Alfred North Whitehead’s philosophy of organism. Next, I present an analysis of contemporary philosophers of biology and their process theories, including the work of Daniel Nicholson and John Dupré, Johanna Seibt, Stephan Guttinger and Thomas Pradeu. Lastly, I provide arguments regarding the relevance of Whitehead’s philosophy to contemporary philosophers of biology and their process philosophies. Part of this analysis will involve comparisons of these views with generally accepted process qualities distilled from contemporary process philosophers such as Nicholas Rescher, Didier Debaise and George Lucas. The thesis makes the positive claim that Whitehead’s philosophical contributions are still relevant to contemporary process philosophers of biology, beyond what is currently recognised. If Whitehead’s arguments were to be taken more seriously, this would strengthen the arguments of contemporary process philosophy in the domain of philosophy of biology.
Keywords: Alfred North Whitehead; Process Philosophy; Philosophy of Biology; Philosophy of Science; Philosophy of Organism; History of Process Philosophy; Process Ontology; Process Epistemology; Integrated Systems; Biological Identity; Immuniology; Biological Mechanism; Logical Construction; 500204 History and philosophy of science